Factors Affecting the Income of Street Vendors Around the Barito Bridge. - Ahmad Maulana; Syaharuddin Syaharuddin; Rusmaniah Rusmaniah; Raihanah Sari; Muhammad Rezky Noor Handy (Journal of Social Development, 2023)
The purpose of this study is to find out what factors affect the income of street vendors around the Barito Bridge. Descriptive techniques are used in this study's qualitative methodology. The methods used to gather the data were observation, interviewing, and documentation. Data sources include both primary and indirect sources. The primary source of data for this study was street vendors who served as research participants. secondary information gleaned from various book reviews. The findings of this research show that the following are the main factors influencing the income of street vendors near the Barito Bridge (1) the initial capital used by street vendors to open a business is different. The greater the mode, the greater the income earned, (2) the trader's working hours or the length of time trading. The longer the trading time the greater the income earned, (3) work experience is very influential on the success of traders in earning income. The more experience, the management and trading strategy will be better. These elements favorably affect how much money street sellers make near the Barito bridge.